Surgical management of recurrent giant retroperitoneal liposarcoma: a challenging surgery - Pegu, Niju; Purkayastha, Joydeep; Talukdar, Abhijit; Nyuwi, Kuotho Y. (International Surgery Journal, 2019)
Retroperitoneal liposarcoma is a rare malignant disease with a high rate of recurrence. Retroperitoneal liposarcoma is usually asymptomatic until the liposarcoma is large enough to compress the surrounding organs and usually presented with compressive symptoms. Main modality of the treatment is surgery both in primary and recurrence cases. Even with complete removal of the liposarcoma, local recurrence rate is very high. Till now, there is currently no evidence that chemotherapy or radiotherapy improve survival rates. Successful complete resection of recurrent retroperitoneal liposarcoma is the sole chance of cure and may increase the 5-year survival rate. In recurrent case, it is challenging for the operating surgeon because of the altered anatomy, adherent to adjacent organs and large vessels and the huge size of the recurrent tumour. The aim of the present study is to report a giant recurrent retroperitoneal liposarcoma and its challenging surgical management.